IMPACT OF GROUNDWATER LEVEL AND ITS PERIODIC FLUCTUATIONS ON LANDSLIDE SLOPE STABILITY (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
A map of groundwater freatic surface for some landslide-prone regions of Armenia has been compiled in GIS. Archival materials were used, as well as fund materials of more than 10000 wells, geomorphological and hydrogeological data, data on the river network and watersheds. Having revealed some relationship between the depth of the groundwater and distribution of landslides the presented map allows to highlight a stable and risky terrains. Danger of landslides is high in the terrains with a shallow groundwater, and vice versa. At the same time, it is necessary to take into account the impact of periodic fluctuations of groundwater level on the landslide development. It is due to periodic changes in the stress state of the landslide mass. Given the above, sites with periodic fluctuation of groundwater level can be considered dangerous and unstable.
Keywords: GIS; interpolation; modeling; groundwater; gradient zones